Silk fibroin/chitosan hydrogel with antibacterial, hemostatic and sustained drug‐release activities. Issue 12 (23rd July 2021) - Xu, Zhangpeng; Chen, Tuying; Zhang, Ke‐Qin; Meng, Kai; Zhao, Huijing
Abstract: Hydrogels are viable wound dressing materials that have gained increasing attention due to their specific physicochemical properties, biocompatibility and environmental responsiveness. In addition to keeping a wound area moist, hydrogels characterized by a porous network structure and regulated drug‐release capacity promote the various phases of wound healing by effectively loading a drug and inducing anti‐infection activity. In this study, we prepared a multifunctional hydrogel with antibacterial, hemostatic and sustained drug‐release activities by chemically crosslinking silk fibroin (SF) and chitosan (CS) biomacromolecules. Results of characterization revealed that the synthesized hydrogel presents higher swelling and in vitro degradation rates under acidic conditions than in a neutral environment. Moreover, the three‐dimensional network structure of the material and the transformation of the SF secondary structure resulted in enhanced compressive mechanical properties (maximum compressive stress of 50–130 kPa). In vitro studies of drug loading and release, antibacterial assay, cytotoxicity studies, and coagulation assay were performed. Results showed that the prepared hydrogel exhibits good bacteriostatic and hemostatic properties, and it is not toxic towards human skin fibroblasts. Therefore, the designed SF/CS hydrogel constitutes an excellent candidate material for wound dressings. © 2021 Society of Industrial Chemistry. Abstract : Chemically crosslinked silk fibroin (SF) and chitosan (CS) biomacromolecules resulted in a multifunctional hydrogel with antibacterial, hemostatic and drug‐release activities.